Development and physico‐mechanical behavior of LDPE–sisal prepreg‐based composites. Issue 5 (27th March 2013) - Dwivedi, U.K.; Hashmi, S.A.R.; Naik, A.; Joshi, R.; Chand, N.
Abstract Low‐density polyethylene (LDPE)‐coated sisal fiber prepreg was prepared by using solution coating process. These coated fiber prepregs were consolidated to make composites having different weight fraction of sisal fibers in a hot compression‐molding machine. This experimental study reveals that higher loading of sisal fiber up to 57wt% in LDPE–sisal composites is possible by this technique. Mechanical and abrasive wear characteristics of these composites were determined. The tensile strength of composites increased with the increase in sisal fiber concentration. Coating thickness of LDPE was varied by changing the viscosity of LDPE–xylene solution that manifested to different weight fraction of fiber in sisal–LDPE composites. Mechanical, dynamic mechanical, and abrasive wear characteristics of these composites were determined. The tensile strength and modulus of sisal composites reached to 17.4 and 265 MPa, respectively, as compared to 7.1 and 33MPa of LDPE. Storage modulus of sisal composites LD57 reached to 2.7 × 109 MPa at 40°C as compared to 8.1 × 108 MPa of LDPE. Abrasive wear properties of LDPE and its composites were determined under multi‐pass mode; pure LDPE showed minimum specific wear rate. The specific wear rate of composites decreased with the sliding distance. Increase of coated sisal fiber content increased the specific wear rate at all the sliding distances, which has been explained on the basis of worn surface microstructures observed by using SEM. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers